2022
DOI: 10.1038/s41598-022-08227-8
|View full text |Cite
|
Sign up to set email alerts
|

Robo4 is constitutively shed by ADAMs from endothelial cells and the shed Robo4 functions to inhibit Slit3-induced angiogenesis

Abstract: Roundabout 4 (Robo4) is a transmembrane receptor that expresses specifically in endothelial cells. Soluble Robo4 was reported in the human plasma and mouse serum and is inhibitory towards FGF- and VEGF-induced angiogenesis. It remains unknown how soluble Robo4 is generated and if soluble Robo4 regulates additional angiogenic signaling. Here, we report soluble Robo4 is the product of constitutive ectodomain shedding of endothelial cell surface Robo4 by disintegrin metalloproteinases ADAM10 and ADAM17 and acts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…In ADAM17flox/flox/Tie2-Cre mice, loss of endothelial ADAM17 inhibits chord formation and impedes ectopic injected tumor growth (138). In endothelial cells, soluble Robo4 (sRobo4) is shed and released by ADAM1, which subsequently inhibits SLIT3-induced angiogenesis (248). Meanwhile, SLIT3 obstructs Robo4 shedding and enhances its signal transduction (248).…”
Section: Regulation Of Endothelial Cells By Adam17mentioning
confidence: 99%
See 1 more Smart Citation
“…In ADAM17flox/flox/Tie2-Cre mice, loss of endothelial ADAM17 inhibits chord formation and impedes ectopic injected tumor growth (138). In endothelial cells, soluble Robo4 (sRobo4) is shed and released by ADAM1, which subsequently inhibits SLIT3-induced angiogenesis (248). Meanwhile, SLIT3 obstructs Robo4 shedding and enhances its signal transduction (248).…”
Section: Regulation Of Endothelial Cells By Adam17mentioning
confidence: 99%
“…In endothelial cells, soluble Robo4 (sRobo4) is shed and released by ADAM1, which subsequently inhibits SLIT3-induced angiogenesis (248). Meanwhile, SLIT3 obstructs Robo4 shedding and enhances its signal transduction (248). ADAM17 may disrupt the barrier effect of vascular endothelial cells by affecting their attachment and tight junctions (249).…”
Section: Regulation Of Endothelial Cells By Adam17mentioning
confidence: 99%
“…Taken together, the results of the RNA-seq bioinformatic analysis, qRT-PCR validation, and IHC confirmed that SLIT3 may be involved in regulating angiogenesis of EP villi. Next, we validated the target gene ROBO4 ( Xiao et al., 2022 ), which is downstream of SLIT3 and reportedly associated with angiogenesis, via qRT-PCR. This assay indicated that relative expression of ROBO4 was statistically lower in EP than in NP villous tissue ( p = 0.007) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another study revealed that SLIT2 is expressed in extravillous trophoblasts (EVTs) of tubal pregnancy, and that changes in SLIT2 expression are linked to vascular remodeling of the fallopian tube ( Li et al., 2015 ). SLIT3 is a new angiogenic factor that binds to ROBO4 , promoting endothelial cell proliferation and migration and inducing angiogenesis in vivo ( Xiao et al., 2022 ; Zhang et al., 2009 ). Moreover, expression of ROBO4 in placental arteries and veins ( Huminiecki et al., 2002 ) and of SLIT3 in the placenta ( Dickinson et al., 2004 ) have been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no research on ROBO4 and pancreatic cancer appears to have been conducted. Numerous studies have shown that ROBO4 stabilizes the vascular network under normal circumstances, which prevents the vasculature from leaking (41)(42)(43). ROBO4 had an effect in various cancers by promoting angiogenesis (44,45).…”
Section: Gene Ratiomentioning
confidence: 99%